Handmade cloning: recent advances, potential and pitfalls. Issue 1 (December 2015) - Verma, Geetika; Arora, JS; Sethi, RS; Mukhopadhyay, CS; Verma, Ramneek
Abstract Handmade cloning (HMC) is the most awaited, simple and micromanipulator-free version of somatic cell nuclear transfer (SCNT). The requirement of expensive micromanipulators and skilled expertise is eliminated in this technique, proving it as a major revolution in the field of embryology. During the past years, many modifications have been incorporated in this technique to boost its efficiency. This alternative approach to micromanipulator based traditional cloning (TC) works wonder in generating comparable or even higher birth rates in addition to declining costs drastically and enabling cryopreservation. This technique is not only applicable to intraspecies nuclear transfer but also to interspecies nuclear transfer (iSCNT) thus permitting conservation of endangered species. It also offers unique possibilities for automation of SCNT which aims at production of transgenic animals that can cure certain human diseases by producing therapeutics hence, providing a healthier future for the wellbeing of humans. The present review aims at highlighting certain aspects of HMC including recent advancements in procedure and factors involved in elevating its efficiency besides covering the potentials and pitfalls of this technique.